Outside Front Cover: Biotechnology Journal 6/2020. Issue 6 (9th June 2020) - Sohn, Yu Jung; Kim, Hee Taek; Baritugo, Kei‐Anne; Jo, Seo Young; Song, Hye Min; Park, Se Young; Park, Su Kyeong; Pyo, Jiwon; Cha, Hyun Gil; Kim, Hoyong; Na, Jeong‐Geol; Park, Chulhwan; et al.
Abstract : Biopolymers produced based on biomasses or plastic wastes by tailor‐made microbial cell factories are one of the promising solutions to solve the current plastic wastes accumulation problems. In this review, development of plastic circular economy via bio‐based and bio/chemical hybrid technologies is discussed. Biopolymers are game changers for the establishment of zero‐waste society.This is reported by Yu Jung Sohn, Hee Taek Kim, Kei‐Anne Baritugo, Seo Young Jo, Hye Min Song, Se Young Park, Su Kyeong Park, Jiwon Pyo, Hyun Gil Cha, Hoyong Kim, Jeong‐Geol Na, Chulhwan Park, Jong‐Il Choi, Jeong Chan Joo, Si Jae Park in article 1900489 .